MATHEMATICS FOR ECONOMICS AND BUSINESS - Jacques, Ian (Pearson, 2023)
"This textbook is intended primarily for students on economics, business studies and management courses. It assumes very little prerequisite knowledge, so it can be read by students who have not undertaken a mathematics course for some time. The style is informal, and the text contains a large number of worked examples. Students are encouraged to tackle problems for themselves as they read through each section. Solutions are provided so that all answers can be checked. Consequently, it should be possible to work through this text on a self-study basis. The material is wide ranging and varies from elementary topics such as percentages and linear equations to more sophisticated topics such as constrained optimisation of multivariate functions. The text should therefore be suitable for use on both low- and high-level quantitative methods courses. This text was first published in 1991. The prime motivation for writing it then was to try to produce a book that students could actually read and understand for themselves. This remains the guiding principle when writing this tenth edition. Extra features and resources requested by students over the years are now incorporated into the printed book. These include end-of-chapter multiple-choice tests and longer examination questions. All of these are designed to help students pass the course. Online resources include access to the eBook and a bank of new problems in MyLab Math. The latter provides students with an interactive learning environment where they can concentrate on topics that they find difficult and measure their own progress. There is a 'help me solve it' mode which provides step-by-step guidance to solve a problem with the system acting like a personal tutor. Lecturer's resources include fully worked solutions to all of the standard problems in the textbook, PowerPoint slides, material on more advanced topics and an introduction to the use of the software packages Excel and Maple in mathematical economics. Many of the examples and questions in this edition have been updated to make them more contemporary. New material on the second-order conditions for Lagrange multipliers and a new section on Lorenz curves and Gini coefficients are provided. Case studies are now included to give an indication how the mathematics covered in each chapter can actually be used by businesses and individuals in practice, which we hope students will find relevant and interesting"